LANDSLIDE AND DEBRIS-FLOW HAZARD ANALYSIS AND PREDICTION USING GIS IN MINAMATA–HOUGAWACHI AREA, JAPAN - Wang Ch.; Esaki T.; Xie M.; Qiu Ch. (My University, 2006)
On July 20, 2003, following a short duration of heavy rainfall, a debris-flow disaster occurred in the Minamata–Hougawachi area, Kumamoto Prefecture, Japan. This disaster was triggered by a landslide. In order to assess the landslide and debris-flow hazard potential of this mountainous region, the study of historic landslides is critical. The objective of the study is to couple 3D slope-stability analysis models and 2D numerical simulation of debris flow within a geographical information systems in order to identity the potential landslide-hazard area. Based on field observations, the failure mechanism of the past landslide is analyzed and the mechanical parameters for 3D slope-stability analysis are calculated from the historic landslide. Then, to locate potential new landslides, the studied area is divided into slope units. Based on 3D slope-stability analysis models and on Monte Carlo simulation, the spots of potential landslides are identified. Finally, we propose a depth-averaged 2D numerical model, in which the debris and water mixture is assumed to be a uniform continuous, incompressible, unsteady Newtonian fluid. The method accurately models the historic debris flow. According to the 2D numerical simulation, the results of the debris-flow model, including the potentially inundated areas, are analyzed, and potentially affected houses, river and road are mapped.
Keywords: LANDSLIDE; DEBRIS FLOW; GEOGRAPHICAL INFORMATION SYSTEMS; NUMERICAL SIMULATION; HAZARD